Biblia brzeska a Europa z perspektywy Mikołaja Radziwiłła „Czarnego” działań o charakterze public relations - Walecki, Wacław (Tematy i Konteksty, 2016)
The article presents the current state of research and outlines plans for further studies on one of the most important translations of the Holy Scriptures into Polish, the so-called Brest Bible, or the Radziwiłł Bible (1563). In the second part, on the basis of Latin sources, the paper analyses the promotion of this edition conducted in Europe by Mikołaj “the Black” Radziwiłł, the initiator of the publication.